Description of eleven new species of phytoseiid mites (Acari: Mesostigmata) from Meghalaya state, north eastern India - Kar, Anamika; Karmakar, Krishna (Zootaxa, 2021)
A survey was done in the state of Meghalaya, India covering East Khasi Hills, West Jaintia Hills and Ri-Bhoi districts during May to July, 2019. During the survey 350 specimens were collected from which 11 new species are described—Amblyseius azaliae sp. nov., Amblyseius meghalayensis sp. nov., Euseius fascae sp. nov., Euseius dwakiensis sp. nov., Okiseius jainticus sp. nov., Okiseius unisetatus sp. nov., Phytoseius clavus sp. nov., Phytoseius aonlae sp. nov., Typhlodromus (Anthoseius) barapanicus sp. nov., Typhlodromus (Anthoseius) campana sp. nov., and Typhlodromus (Anthoseius) cherrapunjiensis sp. nov.